2004
DOI: 10.1002/jnr.20046
|View full text |Cite
|
Sign up to set email alerts
|

Neural precursor cells derived from human embryonic brain retain regional specificity

Abstract: Recent studies have revealed that neural precursor cells can be expanded not only from the subventricular zone and hippocampus but also from other regions of the human embryonic brain. To determine the regional differences of these precursor cells, we divided the brain of a 9-week-old human embryo into four parts, i.e., telencephalon, diencephalon, mesencephalon, and rhombencephalon. All cultures of the tissues yielded neurospheres, and these spheres gave rise to neurons, astrocytes, and oligodendrocytes. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 23 publications
6
45
0
1
Order By: Relevance
“…Telencephalon-derived HNPCs exhibited significantly higher cellfold expansion rates in culture and generated larger-diameter aggregates than cells derived from the ventral mesencephalon, for example. This result is consistent with other data indicating faster proliferation rates in neural precursor cells isolated from more rostral regions of the CNS 33,38,74 and likely reflects a longer period of neurogenesis in the telencephalon. 6,44 The survival of HNPCs in culture and after transplantation into parkinsonian rats varied depending on the region of precursor cell origin.…”
Section: Expansion and Survival Of Hnpcssupporting
confidence: 93%
See 1 more Smart Citation
“…Telencephalon-derived HNPCs exhibited significantly higher cellfold expansion rates in culture and generated larger-diameter aggregates than cells derived from the ventral mesencephalon, for example. This result is consistent with other data indicating faster proliferation rates in neural precursor cells isolated from more rostral regions of the CNS 33,38,74 and likely reflects a longer period of neurogenesis in the telencephalon. 6,44 The survival of HNPCs in culture and after transplantation into parkinsonian rats varied depending on the region of precursor cell origin.…”
Section: Expansion and Survival Of Hnpcssupporting
confidence: 93%
“…Ventral mesencephalon-, brainstem-, and spinal cord-derived HNPCs demonstrated multipotentiality after culture in a variety of media, but the proportions of cells that differentiated into either neuronal or astrocytic immunophenotypes varied depending on the region of precursor cell origin and the manner in which the medium was supplemented. Among the factors that influence the neurogenic capacity of HNPCs are the region of precursor cell origin, which is greater for more rostrally derived cells, 33,38,44 as well as the passage level of the cells, with a decrease in the proportion of neurons and an increase in the proportion of astrocytes over time. 33,38,44 This finding may reflect preferential selection of HNPCs committed to glial phenotypes 38 or a developmental program in which more astrocytes are generated as the brain matures.…”
Section: Differentiation Of Hnpcsmentioning
confidence: 99%
“…Undifferentiated human fetal NSCs transplanted into the SNc of a MPTP ((1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine)-induced primate model of PD were able to survive, integrate and subsequently reduce some behavioral deficits [46]. However, although it has been shown that fetal NSCs can readily differentiate into DA-ergic neurons, a major issue of using these cells is the low yield (1-5%) of generated DA-ergic neurons [46,48,49,50]. Hence, it seems that when compared to ESCs, fetal NSCs are not advantageous when it comes to production of DAergic neurons due to a much-reduced proliferative potential.…”
Section: Fetal Neural Stem Cellsmentioning
confidence: 99%
“…It is well known that Shh, FGF8, Wnts affect the local environment in which mesDA neurons are generated during embryogenesis. However, these molecules underlie the regional specification of several cell types generated in midbrain (MB) and hindbrain during CNS development (Ling et al, 1998;Potter et al, 1999;Storch et al, 2001;Hynes & Rosenthal 1999;Wurst & Bally-Cuif,2001;Lee et al, 2000;Horiguchi et al, 2004) . As a consequence, in addition to mesDA neurons, cultures also include other regionally related neuronal subtypes such as serotonergic and GABAergic neurons (Deacon et al, 1998).…”
Section: Parkinson's Diseasementioning
confidence: 99%